Chitosan/snail slime films as multifunctional platforms for potential biomedical and cosmetic applications: physical and chemical characterization. Issue 12 (11th January 2023) - Gubitosa, Jennifer; Rizzi, Vito; Fini, Paola; Fanelli, Fiorenza; Sibillano, Teresa; Corriero, Nicola; Cosma, Pinalysa
Abstract : Due to the pollution problem, the use of sustainable materials with a reduced environmental impact, such as biocompatible and biodegradable polymers, is growing worldwide in many fields, especially for Life Sciences applications. Abstract : Due to the pollution problem, the use of more sustainable materials with a reduced environmental impact, spanning across biocompatible and biodegradable polymers, is growing worldwide in many different fields, particularly when referring to applications in Life Sciences. Accordingly, with the aim of developing multifunctional materials for potential cosmetic/biomedical purposes, this work reports the physical and chemical characterization of chitosan-based films blended with snail slime, exhibiting antioxidant and sunscreen features. A suitable formulation for preparing free-standing chitosan platforms, mixing low molecular weight chitosan, lactic acid, glycerol, and snail slime into an appropriate ratio, is thus described. The results obtained by morphological analysis and ATR-FTIR spectroscopy, XRD, swelling analysis (also when varying pH, ionic strength, and temperature), and WVTR measurements evidence a uniform distribution of snail slime inside the chitosan network, forming more compacted structures. At first, the UV-Vis analysis is used to investigate the theoretical Sun Protection Factor, finding that these innovative platforms can be used for preventing sunburn. Then, the antioxidant features are investigated using the ABTS assay, displaying a snail slime-mediated and dose-dependent boosted activity.